THE IMPACT OF FOOD QUALITY AND PRICE DISCOUNT TOWARD BRAND IMAGE AND PURCHASE DECISION - Fadilah, Putri; Barkah, Barkah; Erna Listiana; Hasanudin, Hasanudin; Rizky Fauzan (SEAN Institute, 2023)
In today's globalized world, business rivalry is becoming more intense on both a domestic (national) and international level. Currently, the business sector that continues to experience rapid growth is the fast food industry. With the increasing population in Indonesia, the demand for fast food also continues to increase. One example of a fast food product that is popular in Indonesia is KFC. The Indonesian public's view of KFC as a food that has high standards of quality safety, and health has become very strong. When asked about the best place to enjoy fried chicken in Indonesia, KFC always comes up as one of the first choices in their minds. Products produced by this international company offer the assurance of superior food quality. KFC's food quality is an important factor that influences consumer purchase decisions, and this must be the company's focus on improving the quality of its products to win competition in the fast food industry. This study will examine the extent to which the impact food quality and price discounts on purchase decisions, with the brand image as a mediating variable at KFC in Indonesia. In collecting data, this research applied a questionnaire method involving 219 respondents selected through a purposive sampling technique. In data analysis, Structural Equation Modeling (SEM) was used with the help of the AMOS 24 tool. The results of this research reveal that food quality and price discounts have a significant influence on purchase decisions, which are mediated by brand image.